2012
DOI: 10.1186/1745-6215-13-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of embedded and added motor imagery training in patients after stroke: results of a randomised controlled pilot trial

Abstract: BackgroundMotor imagery (MI) when combined with physiotherapy can offer functional benefits after stroke. Two MI integration strategies exist: added and embedded MI. Both approaches were compared when learning a complex motor task (MT): 'Going down, laying on the floor, and getting up again'.MethodsOutpatients after first stroke participated in a single-blinded, randomised controlled trial with MI embedded into physiotherapy (EG1), MI added to physiotherapy (EG2), and a control group (CG). All groups participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 31 publications
1
55
1
2
Order By: Relevance
“…The later studies have similar methodological challenges (8-40 subjects per group) and lead to similar, inconsistent conclusions about the superiority of any 1 specific treatment. [594][595][596][597][598][599][600][601][602][603][604] Likewise, a systematic review of fall prevention after stroke has shown that inconsistencies in outcome measures, intervention type, and implementation in previous research make it difficult to determine the effectiveness of fall prevention programs after stroke. 174 The Prevention of Falls section provides more discussion.…”
Section: Balance and Ataxiamentioning
confidence: 99%
“…The later studies have similar methodological challenges (8-40 subjects per group) and lead to similar, inconsistent conclusions about the superiority of any 1 specific treatment. [594][595][596][597][598][599][600][601][602][603][604] Likewise, a systematic review of fall prevention after stroke has shown that inconsistencies in outcome measures, intervention type, and implementation in previous research make it difficult to determine the effectiveness of fall prevention programs after stroke. 174 The Prevention of Falls section provides more discussion.…”
Section: Balance and Ataxiamentioning
confidence: 99%
“…Motor imagery studies were conducted on several diseases relating to the central nervous system and acute injuries involving orthopedics such as subacute stroke [15][16][17][18][19], chronic stroke [20][21][22], traumatic brain injury [23], multiple sclerosis [23], shoulder impingement syndrome [24], postsurgical anterior cruciate ligament [25], postsurgical flexor tendon repair [26], burn injury [27], phantom limb pain [28], complex regional pain syndrome [28,29], and motor coordination problems [30]. Table 1 lists motor imagery clinical studies found in PubMed.…”
Section: Clinical Studies Of Motor Imagerymentioning
confidence: 99%
“…The effects of motor imagery were observed in upper extremity function in subacute [16] and chronic [23] stroke patients, gait function in subacute [15,18] and chronic [20][21][22] stroke patients, and balance functions in chronic stroke patients [22]. Motor imagery used for motor recovery showed a lack of results in subacute stroke patients with limited upper extremity function [19], stroke patients struggling with goal attainment and Neurological Physical Therapy task performance [17], and those with traumatic brain injury and multiple sclerosis [23]. A possible reason for the different effects of motor imagery is the decline of cognitive function after a patient experiences a stroke.…”
Section: Clinical Studies Of Motor Imagerymentioning
confidence: 99%
“…Nowadays, MT is used mostly as an additional therapy for rehabilitation of paretic hand after stroke Sathian et al, 2000;Ramachandran, 2005;Thieme et al, 2010;Rothgangel et al, 2011;Schuster et al, 2012), even in severe hand paresis (Dohle et al, 2009), in hemiparesis in children (Gygax et al, 2011) but also as a kind of cognitive stimulation in nonused syndrome or neglect syndrome (Beis et al, 2001;Ramachandran et al, 1999) or in deterioration of cognitive functions (Tichelaar Vladimir et al, 2007). There are also studies on surgery intervention in sensory-motor re-education after nerve injuries Lundborg, 2005, 2008;Altschuler and Hu, 2008).…”
Section: Introductionmentioning
confidence: 99%